The gap between users and cataloguers: perception of importance of bibliographic data for required reading and leisure reading (Libellarium: journal for research in the field of information and related sciences, 2021)
This paper provides some insight into cataloguers’ and end users’ perception of the importance of bibliographic data for fiction for two purposes: required reading for school and leisure reading. To obtain information about opinion of cataloguers and users, we used multiple data collection methods: observation, think aloud protocol and in-depth interviews. Four studies were conducted: among 30 cataloguers in June 2014 and 32 cataloguers in February and March 2016, and among 105 high school students in November 2011 and 108 adults in July 2012. The focus was on Slovenian catalogers and users. The results revealed similarities between users’ and cataloguers’ view of the most important bibliographic data for fiction. Finally, we propose attributes, considered as important from cataloguers’ as well as users’ standpoint. Most of them could be included in the bibliographic record, regardless of the cataloguing rules and practice.
Keywords: bibliographic data; cataloguers; information need; library catalogue; users